The African American theatrical body reception, performance, and the stage - Colbert, Soyica Diggs, 1979-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"Presenting an innovative approach to performance studies and literary history, Soyica Colbert argues for the centrality of black performance traditions to African American literature, including preaching, dancing, blues and gospel, and theatre itself, showing how these performance traditions create the 'performative ground' of African American literary texts. Across a century of literary production using the physical space of the theatre and the discursive space of the page, W. E. B. Du Bois, Zora Neale Hurston, James Baldwin, August Wilson and others deploy performances to re-situate black people in time and space. The study examines African American plays past and present, including A Raisin in the Sun, Blues for Mister Charlie and Joe Turner's Come and Gone, demonstrating how African American dramatists stage black performances in their plays as acts of recuperation and restoration, creating sites that have the potential to repair the damage caused by slavery and its aftermath"--
Machine generated contents note: Overture: rites that render repairing: Suzan-Lori Parks' The America Play; 1. Repetition/reproduction: the DNA of black expressive culture: Lorraine Hansberry's A Raisin in the Sun; 2. Recuperating black diasporic history: W. E. B. Du Bois' The Star of Ethiopia; 3. Re-enacting the Harlem Renaissance: Zora Neale Hurston's Color Struck; 4. Resisting shame, offering praise and worship: Langston Hughes's Tambourines to Glory; 5. Resisting death: the blues bravado of a ghost: James Baldwin's Blues for Mister Charlie; 6. Rituals of repair: August Wilson's Joe Turner's Come and Gone; 7. Reconstitution: Suzan-Lori Parks' Topdog/Underdog; Epilogue: Black movements: Tarell Alvin McCraney's In the Red and Brown Water; Bibliography.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: American literature -- African American authors -- History and criticism; African Americans in literature; Electronic books